Climate variability and sardine recruitment in the California Current: A mechanistic analysis of an ecosystem model. (7th August 2018) - Politikos, Dimitrios V.; Curchitser, Enrique N.; Rose, Kenneth A.; Checkley, David M.; Fiechter, Jerome
Abstract: Recruitment varies substantially in small pelagic fish populations. Understanding of the mechanisms linking environment to recruitment is essential for the effective management of fisheries resources. In this study, we used a fully coupled end‐to‐end ecosystem model to study the effect of climate variability on sardine recruitment in the California Current System during 1965–2006. Ocean variability was represented by ROMS hydrodynamic and NEMURO biogeochemical models, and sardine population dynamics was simulated through a full life cycle individual‐based model. Model analysis was designed to elucidate how changes in abiotic and biotic conditions may impact the spawning habitats, early life stage survival, and ultimately recruitment of sardine. Our findings revealed the importance of spatial processes to shape early life stages dynamics. Shifts in spawning habitats were dictated by the spatial variations in temperature and the behavioral movement of adults. Additionally, the spatial match of eggs with warmer temperatures and larvae with their prey influenced their survival. The northward shifts in spawning locations and the accomplishment of good recruitment in warmer years agreed with existing knowledge. Egg production and survival during egg and yolk‐sac larval stages were key factors to drive the long‐term variations in recruitment. Finally, our analysis provided a quantitative assessment of climate impact on year‐to‐year variation in sardine recruitment by integrating multiple hypotheses.